Answer:
4 months
Step-by-step explanation:
-Let the number of months it takes for their heights to equal be x and let h(x) be the height after x months.
#For plant 1, we equate height after x months as:
![h(x)=6+3x](https://tex.z-dn.net/?f=h%28x%29%3D6%2B3x)
#For plant 2, we equate height after x months and at a constant rate m:
![h(x)=2+mx](https://tex.z-dn.net/?f=h%28x%29%3D2%2Bmx)
#we equate and solve for rate of growth, m in plant 2 as below:
![h(x)=2+mx\\\\but\ h(12)=50\\\\\therefore r=\frac{50-2}{12}\\\\r=4 \ inches/month](https://tex.z-dn.net/?f=h%28x%29%3D2%2Bmx%5C%5C%5C%5Cbut%5C%20%20h%2812%29%3D50%5C%5C%5C%5C%5Ctherefore%20r%3D%5Cfrac%7B50-2%7D%7B12%7D%5C%5C%5C%5Cr%3D4%20%5C%20inches%2Fmonth)
#We then equate the two heights after x months to solve for x:
![h(x)_1=h(x)_2\\\\6+3x=2+4x\\\\6-2=4x-3x\\\\x=4](https://tex.z-dn.net/?f=h%28x%29_1%3Dh%28x%29_2%5C%5C%5C%5C6%2B3x%3D2%2B4x%5C%5C%5C%5C6-2%3D4x-3x%5C%5C%5C%5Cx%3D4)
Hence, the plants have the same height after 4 months